Essays on the allocation, effectiveness and coordination of development aid - Öhler, Hannes (2012)
The dissertation contributes to three main topics in the literature on development aid: aid allocation, aid effectiveness and aid coordination. Chapter I assesses the allocation of aid by non-governmental organizations (NGOs). Chapter II analyzes aid allocation decisions within an aid recipient country. Chapter III assesses whether foreign aid specifically meant to fight sexually transmitted diseases has been effective in alleviating HIV/AIDS epidemics in developing countries. Chapter IV investigates the effectiveness of a new form of conditionality, i.e., making aid commitments conditional on past performance. Finally, Chapter V looks at the coordination of donors within an aid recipient country.
Enth. außerdem 5 Sonderabdr
Online publiziert: 2013
Keywords: Hochschulschrift